Peran Guru PAI dalam Pembentukan Karakter Religius Siswa - Sholekah, Umma Rohmah; Fatimah, Meti; Subando, Joko (TSAQOFAH, 2026)
This study aimed to describe the impact of Islamic Religious Education teachers’ roles in shaping students’ religious character. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and then analyzed thematically to identify patterns in teacher roles and forms of students’ religious character development. The findings show that Islamic Religious Education teachers play a strategic role as educators, spiritual guides, and moral exemplars, exerting a significant influence on the formation of students’ religious character. This impact is reflected in increased discipline in religious practice, strengthened social morality, enhanced moral awareness and religious understanding, and the development of students’ self-control in facing negative influences, including those originating from digital media. Character formation is carried out through the integration of cognitive, affective, and behavioral aspects, supported by consistent religious habituation in daily life. A conducive religious education environment and family support further reinforce the internalization of Islamic values in students. Therefore, this study affirms that the success of religious character formation is not determined solely by instructional content, but is strongly shaped by teachers’ role modelling and active involvement, continuous religious habituation, and the synergy between schools and parents.